Ductal Carcinoma In Situ of the Breast in Sclerosing Adenosis Mimicking Microinvasive Ductal Carcinoma: A Rare Case Report - Yu‐Kai Chang; Yuan‐Yuei Chen; Zhi‐Jie Hong; Guo‐Shiou Liao; Jyh‐Cherng Yu (Clinical Case Reports)
ABSTRACT Sclerosing adenosis (SA) is a subtype of adenosis characterized by proliferative adenosis and stromal sclerosis with distortion of the terminal ductal lobular unit. Although SA is the most prevalent benign breast condition among middle‐aged women, it may be associated with a two‐fold increase in breast cancer risk. Microscopic findings of ductal carcinoma in situ (DCIS) in a SA (SA‐DCIS) may mimic microinvasive carcinoma or even invasive carcinoma, which may result in overtreatment by a breast surgeon. Therefore, pathological evaluation must be performed carefully in such cases to establish a definitive diagnosis. Herein, we present a rare case of SA‐DCIS that mimicked microinvasive ductal carcinoma. A 51‐year‐old woman was diagnosed with high‐grade DCIS of the left breast, highly suspicious for microinvasion, based on core biopsy. She underwent mastectomy of the left breast and prophylactic mastectomy of the right breast for personal reasons after imaging evaluation, including mammography and ultrasonography. However, the final diagnosis was bilateral intermediate‐grade DCIS, characterized by the presence of intraductal carcinoma cells exhibiting enlarged hyperchromatic nuclei and a high nuclear‐to‐cytoplasmic ratio within the mammary ducts. However, the diagnosis was incompatible with the initial pathological results. A‐DCIS has pathological features similar to those of microinvasive or invasive carcinomas. Thoroughly evaluating biopsy findings of lesions to distinguish between SA‐DCIS and invasive carcinoma is crucial to prevent overdiagnosis and unnecessary management in patients with DCIS. Patients diagnosed with SA‐DCIS are at a higher risk of developing bilateral breast cancer than those without SA‐DCIS.